2016
DOI: 10.22323/2.15050401
|View full text |Cite
|
Sign up to set email alerts
|

An integrated model of science communication — More than providing evidence

Abstract: Factors that influence reception and use of information are represented in this koru model of science communication using the metaphor of a growing plant. Identity is central to this model, determining whether an individual attends to information, how it is used and whether access to it results in increased awareness, knowledge or understanding, changed attitudes or behaviour. In this koru model, facts are represented as nutrients in the soil; the matrix influences their availability. Communication involves re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
42
0
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 50 publications
(56 citation statements)
references
References 47 publications
0
42
0
1
Order By: Relevance
“…Another likely reason for the group's ongoing activity is its engaging topic, with birds being an important feature of the cultural identity of New Zealanders (Kiwis) cultural identity. Identity, including values and attitudes, is an important determinant of people's engagement with or use of information (Longnecker 2016). A citizen science project with a less-engaging area of focus might find it more challenging to support its participants in this way.…”
Section: Discussionmentioning
confidence: 99%
“…Another likely reason for the group's ongoing activity is its engaging topic, with birds being an important feature of the cultural identity of New Zealanders (Kiwis) cultural identity. Identity, including values and attitudes, is an important determinant of people's engagement with or use of information (Longnecker 2016). A citizen science project with a less-engaging area of focus might find it more challenging to support its participants in this way.…”
Section: Discussionmentioning
confidence: 99%
“…While an important element, this ignores a growing understanding within science communication that facts alone are not enough to convince someone to adopt behaviours or accept ideas [Bray, France and Gilbert, 2012;Longnecker, 2016]. Studies have shown that addressing misinformation about vaccination with more 'education' is usually ineffective [Kata, 2010].…”
Section: Discussionmentioning
confidence: 99%
“…A copy of a document that complemented the talk with graphs, statistical analyses and a brief report of preliminary results was available for all who wished to take away. The values of different parties were taken into account since values play a key role in whether people engage with information and how they do this (Longnecker 2016).…”
Section: 'Get Together'mentioning
confidence: 99%